Factors activating the development of towns with a spa and touristic character in Lower Silesia during 2015-2019 - Rogowska-Sawicz, Małgorzata (Czynniki aktywujące rozwój miast o charakterze uzdrowiskowym i turystycznym na Dolnym Śląsku w latach 2015-2019, 2021)
The study examined the development process of towns in the Polish region Lower Silesia. It analysed seven units with a very specific function – spa and tourist resort. The final comparison considered the period of 2015-2019. The conducted analysis was based on a taxonomic method that examined local explanatory factors towards the territorial aspect of development. The initial research findings show that towns can be an important link in regional settlement units, but only those who developed specific endogenous functions are performing well and respond to changing economic patterns and economic globalisation. In this case spa and touristic character were analysed.
Biblioteka Regionalisty, 2021, Nr 21, s. 124-135
Keywords: social and economic development; territorial capital; resort towns; spa and touristic town; rozwój lokalny; kapitał terytorialny; uzdrowisko